1985
DOI: 10.1095/biolreprod32.1.155
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Rat Epididymal Sperm Adenosine 3′,5′-Monophosphate-Dependent Protein Kinases: Maturation Differences and Cellular Location

Abstract: The photoaffinity analog [32P]8-N3 cAMP (8-azido adenosine 3',5'-monophosphate was used to analyze the membrane sidedness of rat sperm cAMP binding proteins during epididymal maturation. Evidence is presented here which supports the hypothesis that 35-45% of the regulatory subunits of the Type I and Type II cAMP-dependent protein kinases are readily available to externally added cyclic nucleotide. It was observed by sodium dodecyl sulfate gel electrophoresis (SDS-PAGE) and autoradiography that only two rat spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

1985
1985
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
1
18
2
Order By: Relevance
“…The primary bases of this conclusion with rat epididymal sperm are that approximately 30% of the cells are leaky, as shown by assays of cytosolic enzyme markers, and that all the CAMP-binding proteins are available to externally added 8-[32P]-N, cAMP and a-chymotrypsin. In contrast to this report, Atherton et al [4] observed that approximately 60% of CAMP-binding proteins of intact spermatozoa require sonication to be readily available to 8-[32P]--N, cAMP or proteolytic enzymes. They also confirmed the intactness of spermatozoa by assaying hexokinase as a marker enzyme [4].…”
Section: Sperm Surface Macromoleculescontrasting
confidence: 84%
See 2 more Smart Citations
“…The primary bases of this conclusion with rat epididymal sperm are that approximately 30% of the cells are leaky, as shown by assays of cytosolic enzyme markers, and that all the CAMP-binding proteins are available to externally added 8-[32P]-N, cAMP and a-chymotrypsin. In contrast to this report, Atherton et al [4] observed that approximately 60% of CAMP-binding proteins of intact spermatozoa require sonication to be readily available to 8-[32P]--N, cAMP or proteolytic enzymes. They also confirmed the intactness of spermatozoa by assaying hexokinase as a marker enzyme [4].…”
Section: Sperm Surface Macromoleculescontrasting
confidence: 84%
“…In contrast to this report, Atherton et al [4] observed that approximately 60% of CAMP-binding proteins of intact spermatozoa require sonication to be readily available to 8-[32P]--N, cAMP or proteolytic enzymes. They also confirmed the intactness of spermatozoa by assaying hexokinase as a marker enzyme [4].…”
Section: Sperm Surface Macromoleculescontrasting
confidence: 84%
See 1 more Smart Citation
“…Protein kinase activities in semen are associated with both spermatozoa (Hoskins et al, 1972;Garbers et al, 1973;Majumder, 1978a;Tash & Means, 1982;Horowitz et al, 1984;Atherton et al, 1985) and seminal plasma (Majumder, 1978b;Fabbro et al, 1982;. Approxi¬ mately 70-80% of the protein kinase activities in seminal plasma are correlated with the number of spermatozoa originally present in the ejaculate (Fabbro et al, 1982;Wilson & Kaye, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the azido cAMP analogue ['2P]8N3cAMP is an excellent probe for the study of epididyma1 sperm maturation [2]. Since epididymal sperm maturation confers fertilizing ability on sperm, the process is important to both contraceptive and infertility research.…”
Section: Introductionmentioning
confidence: 99%